Cardiff after dark - Dakowicz, Maciej (London : Thames & Hudson, 2012)
A monograph by a British-based Polish photographer who spent five years photographing the nighttime revelries that take place in Cardiff over the weekend. Focused around a few pedestrianized streets in the city centre, it features images that capture nightlife fueled by alcohol and emotions.
boek
Keywords: Dakowicz, Maciej